Faktor yang Berhubungan dengan Kepuasan Pelayanan Kesehatan di Puskesmas Putri Ayu Kota Jambi - Fithriyani Fithriyani; Miko Eka Putri (Jurnal Akademika Baiturrahim Jambi, 2026)
Patient satisfaction is an important indicator of the quality of health services in primary facilities such as health centers because it reflects the extent to which services meet the expectations and needs of patients. This satisfaction not only determines clinical success but also affects public trust in public health services and the regularity of patient visits. The health facility that is widely used by the community is the Health Center.Puskesmas The success of health services is seen from community satisfaction which is also a benchmark for service quality in an effort to improve health. The study aimed to find out the factors related to health service satisfaction at the Putri Ayu Health Center, Jambi City. Satisfaction factors include tangible, reliability, responsiveness, assurance and emphaty. Samples were carried out to people who visited the Putri Ayu health center in Jambi City in 2024 with an accidental sampling technique  with a total of 48 people. The research was conducted from October 2024 to August 2025 at the Putri Ayu Health Center. The research design used was descriptive analysis with univariate and bivariate data analysis. The results of the univariate analysis were obtained by Tangible with the Satisfied category 66.7%, Reliability with the Satisfied category 58.3%, responsiveness with the Satisfied category 66.7%, Assurance with the Satisfied category 79.2% and emphaty with the Satisfied category 66.7% and the bivariate analysis found that there was a relationship between Tangible, Reliability, Responsiveness, Assurance and Emphaty with satisfaction in health services. The conclusion of the study was obtained that more than most of the factors in the satisfaction category and there was a relationship between factors related to satisfaction of health services. Suggestions for the Putri Ayu Health Center to optimize services to the community so that they can increase community satisfaction with health services